Give Them Some Slack—They’re Trying to Change! The Benefits of Excess Cash, Excess Employees, and Increased Human Capital in the Strategic Change Context - Bentley, F. Scott; Kehoe, Rebecca R. (Academy of Management Journal, 2020)
We address calls for contextualization in the study of slack resources by examining the pursuit of strategic change as a contingency that shapes the effects of human resource (HR) slack and financial slack on firm performance. Using data on U.S. commercial banks from 2002 to 2014, we demonstrate that HR slack is more positively related to firm performance in firms pursuing strategic change, and that this relationship is stronger in the presence of greater financial slack. Moreover, we find that the moderating effect of financial slack on HR slack in the strategic change context operates through changes in organizations’ human capital investment, offering a unique examination of a key mechanism through which slack resources create value and through which complementarities between different types of slack come to fruition. Our paper advances the contingency perspective within the slack literature and brings important insights from the resource management perspective to the conversation on slack and performance.